Dianthus caryophyllus L. Selection of Culophyllus L. Cultivars Differentiated from Calas Cultivars resistant to Fusarium oxysporum - Adnan Abdullah; Nadeem Ramadan (College of Education for Pure Sciences, 2008)
Abstract In this study callas stimulated from cotyledons explants of carnation seedlings cultured on MS media supplemented with 0.1 mg/L of BA and 0.5 mg/L of 2,4-D was used . The ability of cotyledons callus for regeneration on MS media supplemented with different concentrations (0.5-3.0 ) mg/L of BA combined with different concentrations ( 0.1-1.0) mg/L of NAA or 2,4-D was tested . The best regeneration medium was MS with 2.5 mg/L of BA and 0.5 mg/L of NAA . Selection of resistant callus to the virulent strains of Fusarium oxysporum. f.sp. diunthi was examined from culture medium contained the concentrations 2.5, 5.0 , 7.5, 10.0 12.5,15.0,17.5 . 20.0 and 25% of fungal filtrates. The concentrations which allowed selection after three cycles (20 days /cycle) of selection were 12.5 and 15.0% . The resistant callus showed a high level of peroxidases enzymes activity . Carnation plants which regenerated from callus of cotyledons were resistant the toxic effect of fungal filtrate, in spite of reduction of the regeneration ability of the resistant callus up to 43.7% compared with the control plants . Carnation plant regenerated from tolerante callus exhibited clear resistance when inoculated with the virulent fungi .